Neurological complications of infective endocarditis - a review - Stanicki, Paweł; Szarpak, Julita; Pażyra, Aldona; Kusak, Natalia; Żak, Natalia; Jaworska, Barbara (Quality in Sport, 2024)
Introduction and purpose Infective endocarditis (IE) is a disease resulting from infection of the endocardium. In addition to cardiac symptoms, frequent complications of IE include various damage to the nervous system. The aim of this study is to describe the current state of knowledge about the neurological complications of infective endocarditis. Methods Medical publications were reviewed using the "PubMed" and "Google Scholar" databases. The obtained results were verified in terms of the following criteria: publication in 2016, retrospective analysis, obtaining 44 papaers covering a total of 8067 patients. The information was supplemented with case reports and meta-analyses. Description of the state of knowledge Neurologic complications occur in 20 to 60% of patients with IE. The most common is ischemic stroke, the symptoms of which may precede the diagnosis of IE. Less common complications that often remain asymptomatic include mycotic aneurysms and intracranial hemorrhages. Infectious material entering the brain may also cause meningitis and brain abscess. However, these complications do not occur often. Magnetic resonance imaging of the head is an effective test for detecting neurological damage in the course of IE. The recommendation for routine use of this test is debatable. In addition to antibiotic therapy, cardiac surgery is used to treat IE to remove bacterial vegetation. Research indicates the high effectiveness of this type of surgery in the prevention and treatment of neurological complications of infective endocarditis.